Kreativitas Guru Sekolah Minggu Dalam Meningkatkan Spiritual Anak Melalui Metode PAIKEM - Ester Debora Br Siburian; Viktor Deni Siregar; Yolenta Erika (Jurnal Pendidikan Agama dan Teologi, 2023)
The purpose of this writing is to increase the spirituality of Sunday School Children (ASM) by applying the Active, Innovative, Creative, Effective, and Fun Learning (PAIKEM) method in attending Sunday school services. The method used in this study is qualitative with a descriptive library approach. By collecting data through books, nationally indexed articles, even interviews, which are then analyzed so that results are found and conclusions are drawn. Sunday school is a very important part of church life which is devoted to children. Sunday school children are the future generation of Christian congregations who must be taught the Word of God. The parties involved in teaching the Word of God to Sunday school children are the church board and especially the Sunday school teachers.